2011
DOI: 10.3920/bm2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in protein metabolism of the probiotic lactic acid bacterium Lactobacillus delbrueckii UFV H2b20

Abstract: A basic requirement for the prediction of the potential use of lactic acid bacteria (LAB) in the dairy industry is the identification of specific genes involved in flavour-forming pathways. The probiotic Lactobacillus delbrueckii UFV H2b20 was submitted to a genetic characterisation and phylogenetic analysis of genes involved in protein catabolism. Eight genes belonging to this system were identified, which possess a closely phylogenetic relationship to NCFM strains representative, as it was demonstrated for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…LAB have an efficient proteolytic system composed of a cell envelope proteinase (which initiates protein degradation), a transport system and several intracellular peptidases. In this respect, certain LAB are able to degrade milk proteins (Do Carmo et al, 2011;Hebert et al, 2008). Moreover, Je ˛drychowski and Wróblewska (2005) have shown that milk fermentation by LAB could reduce 99% of some whey protein allergenicity; however, immunoreactivity of BLG was only slightly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…LAB have an efficient proteolytic system composed of a cell envelope proteinase (which initiates protein degradation), a transport system and several intracellular peptidases. In this respect, certain LAB are able to degrade milk proteins (Do Carmo et al, 2011;Hebert et al, 2008). Moreover, Je ˛drychowski and Wróblewska (2005) have shown that milk fermentation by LAB could reduce 99% of some whey protein allergenicity; however, immunoreactivity of BLG was only slightly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria hydrolyze CN to produce all AA except glutamic acid and cysteine. In particular, L. bulgaricus can produce large amounts of proline, lysine, and valine (Do Carmo et al, 2011). In addition, L. bulgaricus has a complex lactose-degrading enzyme system that can efficiently convert lactose to lactic acid (Burgos-Rubio et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several proteolytic enzymes have been identified for Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus ; also, the whole proteolytic system of Lactococcus lactis and several lactobacilli species has been well characterized (Liu et al 2010; Do Carmo et al 2011).…”
mentioning
confidence: 99%